1998
DOI: 10.1007/s004410051166
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a diazepam-binding inhibitor (DBI) benzodiazepine receptor-like mechanism in ecdysteroidogenesis by the insect prothoracic gland

Abstract: The diazepam-binding inhibitor (DBI) is a 10-kDa highly evolutionarily conserved multifunctional protein. In mammals, one of DBI's functions is in the activation of steroid hormone biosynthesis via binding to a specific outer mitochondrial membrane receptor (benzodiazepine receptor, BZD) and promoting cholesterol transport to the inner membrane. In this work, a multitiered approach was utilized to study the role of this receptor-like activity in ecdysteroidogenesis by larval insect prothoracic glands (PGs). Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 38 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…This indicates that ACBP is expressed in an allele dosage-dependent fashion from both alleles. The immunohistochemical detections revealed that ACBP is distributed evenly in the hepatocytes from ACBP ϩ/ϩ liver and that ACBP is present both in the cytosol and in the nucleus as has been reported for other cell types (57)(58)(59)(60). Importantly, ACBP staining is completely absent from the liver of ACBP Ϫ/Ϫ mice, thereby demonstrating the specificity of the antibody.…”
Section: Resultssupporting
confidence: 70%
“…This indicates that ACBP is expressed in an allele dosage-dependent fashion from both alleles. The immunohistochemical detections revealed that ACBP is distributed evenly in the hepatocytes from ACBP ϩ/ϩ liver and that ACBP is present both in the cytosol and in the nucleus as has been reported for other cell types (57)(58)(59)(60). Importantly, ACBP staining is completely absent from the liver of ACBP Ϫ/Ϫ mice, thereby demonstrating the specificity of the antibody.…”
Section: Resultssupporting
confidence: 70%
“…For instance, cholesterol transport into mitochondria is the rate-determining step in steroidogenesis (8,11). TSPO serves the similar function in plants (12), insects (13), and mammals (14). However, the appearance of the drug, such as the benzodiazepine diazepam, binding sites on TSPO evolved later than the brain-specific ␥-aminobutyric acid A receptor benzodiazepine binding sites (15), although drug binding was observed in both the plant and insect TSPOs (12,13).…”
Section: Translocator Protein (Tspo)mentioning
confidence: 99%
“…TSPO serves the similar function in plants (12), insects (13), and mammals (14). However, the appearance of the drug, such as the benzodiazepine diazepam, binding sites on TSPO evolved later than the brain-specific ␥-aminobutyric acid A receptor benzodiazepine binding sites (15), although drug binding was observed in both the plant and insect TSPOs (12,13). Thus, throughout evolution, mammalian Tspo genes have exhibited extraordinary plasticity, a valuable trait to be further exploited.…”
Section: Translocator Protein (Tspo)mentioning
confidence: 99%
“…Acyl-CoA is transported in the cytoplasm by specific acyl-CoA-binding proteins (ACBP) (Knudsen et al, 2000). ACBP has been identified in the midgut and prothoracic gland of M. sexta (Snyder and Van Antwerpen, 1997;Snyder and Van Antwerpen, 1998), as well as in different tissues of D. melanogaster, including the oocyte (Kolmer et al, 1994). Northern blot analysis has indicated that the ovaries of M. sexta also express ACBP (Snyder and Feyereisen, 1993), indicating the possible involvement of this protein in the cytosolic transport of acyl-CoAs in oocytes of M.sexta.…”
Section: Intracellular Lipid Transportmentioning
confidence: 99%